Sustaining mental health and wellbeing programmes in schools: recommendations from an online roundtable - March, Anna; Stapley, Emily; Hayes, Daniel; Moore, Darren; Deighton, Jessica (Frontiers in Education, 2024)
Despite recent investments in school-based mental health and wellbeing promotion in England, the sustainability of mental health interventions remains a substantial challenge. This article brings together potential solutions to sustaining interventions in schools, drawing on insights from an online roundtable discussion held in July 2022. Facilitated by researchers and informed by recent research on barriers and facilitators to sustaining school-based mental health interventions, 16 participants came together to discuss challenges and solutions. Participants included school staff, policy makers, educational psychologists, researchers and mental health intervention developers. The discussion explored the need for accountability at all levels (e.g., from school leaders to policy makers and Ofsted) and the potential value of engaging schools more consistently with academic evidence. Participants also discussed the importance of creating a healthy and sustainable ecosystem for interventions (underscoring the significance of staff wellbeing, adequate resourcing, and longer-term funding commitments), and moving beyond separate, isolated interventions. The findings offer a range of recommendations for school decision makers, mental health researchers, intervention developers, and those working in the wider system around schools.